Word Class Category Phrases in the Short Story "Wanita Berwajah Penyok" by Ratih Kumala - Siti Risamawarni; Ika Wisma Wardani; Indah Setia Margaretta; Asy Syifa Khoirunnis; Yanti Sariasih (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Short stories women are the work of faceless dent literature part of a kumala on 6 February published in 2005 in the newspaper Compass. In the syntactic study, any piece of literature has phrases in all its contents. A phrase combines two or more words unrelated to the predicate element. The short story The Dented Face by Ratih Kumala has many phrases. Furthermore, the category of word classes that underlie the formation of types of phrases. This study aims to analyze and describe the phrases contained in the short story Women With Dent Faces by Ratih Kumala based on word class category. The source of this research data is Ratih Kumala's Short Story of a Dented Faceted Woman. Data collection techniques are carried out using note-reading techniques that are analyzed using qualitative descriptive methods. The results of this study are 1) the short story The Dented-Faced Woman by Ratih Kumala contains the phrases noun, verb, adjective, adverb, numeralia, prepositional, and prepositions. 2) Data on noun phrases of as many as 16 data, verb phrases of as many as 6 data, adjective phrases of as many as 8 data, adverb phrases of as many as 3 data, and prepositional phrases of as many as 4 data.